Clinical role of a new prognostic score using platelet-to-lymphocyte ratio in patients with malignant pleural mesothelioma undergoing extrapleural pneumonectomy - Tagawa, Tetsuzo; Anraku, Masaki; Morodomi, Yosuke; Takenaka, Tomoyoshi; Okamoto, Tatsuro; Takenoyama, Mitsuhiro; Ichinose, Yukito; Maehara, Yoshihiko; Cho, B. C. John; Feld, Ronald; Tsao, Ming-Sound; Leighl, Natasha; et al. (Journal of Thoracic Disease, 2015)
Background: To investigate the prognostic value of platelet-to-lymphocyte ratio (PLR) and create a new prognostic score in patients with malignant pleural mesothelioma (MPM) undergoing extrapleural pneumonectomy (EPP). Methods: Of 85 patients who underwent EPP for MPM over 10 years at Toronto General Hospital, 65 patients whose blood test results before initial therapy were available were retrospectively analyzed as a training cohort to identify and develop a prognostic score. Receiver operating characteristic (ROC) analysis was performed to examine cutoff values of hematologic parameters for survival. The prognostic score was externally validated in a cohort of 32 patients who underwent EPP for MPM over 13 years at two institutes in Japan. Results: In the training cohort, multivariate analysis confirmed sex (P=0.0053) and PLR (P=0.049) as independent predictors of overall survival. The prognostic score was established using sex and PLR. The score was defined as follows: female:male =0:1 point; PLR 215=0:1 point. The patients were classified into three risk groups according to the sum of the points: risk 0 (0 point), 1 (1 point), and 2 (2 points). Median survival time of the patients in the training cohort according to the risk groups were not reached, 32.0 and 19.4 months for risk 0 (n=6), 1 (n=36) and 2 (n=23), respectively (P=0.0006). In the validation cohort, median survival time was not reached, 45.9 and 14.5 months for risk 0 (n=4), 1 (n=18) and 2 (n=10), respectively (P=0.0002). Conclusions: The new prognostic score using PLR is simple and useful for predicting the prognosis of patients with MPM undergoing EPP. Further study should be done to examine the role of this scoring system to optimize treatment strategy.